Management, Husbandry and Milk Production in Dairy Farms in Khartoum State - H. A. A., Mohamed; I. E. M, El Zubeir; A. A, Fadlelmoula (Journal of Veterinary Medicine and Animal Production, 2022)
This study was designed to assess current situation of dairy farms in Khartoum State – Eastern Nile area. Sixty dairy farms were selected randomly and the owners were directly interviewed using structural questionnaire during the period of March to June 2010. High significant (P<0.001) differences were obtained in the educational levels of farm’s owners, which showed significant positive correlation (P<0.05) with the number of labours (r=0.264) and veterinary supervision (r=0.273). The majority of the farms were constructed on private basis without conducting feasibility study (r=-0.369; P<0.01) and managed by unprofessional owners (r= -0.275; P<0.01), who don’t insure against their herds and received little extension services. Specialized dairy farming represent 38.33% of dairy farming followed by diversified (36.67%) and integrated farming (25%). The predominant herds were cross cows (95%). Record keeping was practiced in 36.33% of the farms. The natural mating (48.33%) was the common method for herds’ insemination and all farmers (100%) practiced hand milking twice a day. The building materials consist of wooden roof (66.67%), zink fences (35.59%) and sandy floor (93.33%). Regarding the application of preventive measurements and control of the diseases, only 18.33% of the farms had resident veterinarian and rarely (28%) vaccinate their herds against diseases. PositiveThis study was designed to assess current situation of dairy farms in Khartoum State – Eastern Nile area. Sixty dairy farms were selected randomly and the owners were directly interviewed using structural questionnaire during the period of March to June 2010. High significant (P<0.001) differences were obtained in the educational levels of farm’s owners, which showed significant positive correlation (P<0.05) with the number of labours (r=0.264) and veterinary supervision (r=0.273). The majority of the farms were constructed on private basis without conducting feasibility study (r=-0.369; P<0.01) and managed by unprofessional owners (r= -0.275; P<0.01), who don’t insure against their herds and received little extension services. Specialized dairy farming represent 38.33% of dairy farming followed by diversified (36.67%) and integrated farming (25%). The predominant herds were cross cows (95%). Record keeping was practiced in 36.33% of the farms. The natural mating (48.33%) was the common method for herds’ insemination and all farmers (100%) practiced hand milking twice a day. The building materials consist of wooden roof (66.67%), zink fences (35.59%) and sandy floor (93.33%). Regarding the application of preventive measurements and control of the diseases, only 18.33% of the farms had resident veterinarian and rarely (28%) vaccinate their herds against diseases. Positive